2021
DOI: 10.3389/fneur.2021.626399
|View full text |Cite
|
Sign up to set email alerts
|

Education, Training, and Practices of Neurorehabilitation in India During the COVID-19 Pandemic

Abstract: Background: Corona virus disease (COVID-19) was declared a pandemic by the World Health Organization in March 2020. This has affected service delivery among all medical disciplines in India including neurorehabilitation services.Aims and Objectives: The aims and objectives of the study were to assess the effect of COVID-19 pandemic on neurorehabilitation services across India.Methodology: A prospective nationwide survey study was undertaken by the Indian Federation of Neurorehabilitation during the pandemic. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…A review of home-based tele-rehabilitation services in Southeast Asian countries found that the completion rates of interventions accessed by people with disabilities have been ~80% in China and South Korea ( 15 ). A recent survey from the sub-continent (India) had showed close to 80% of the rehabilitation facilities with basic tele-rehabilitation infrastructure ( 16 ). However, tele-health and rehabilitation services are not available and are poorly utilized by the government primary care systems in many countries in the region of Sub-Saharan Africa ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of home-based tele-rehabilitation services in Southeast Asian countries found that the completion rates of interventions accessed by people with disabilities have been ~80% in China and South Korea ( 15 ). A recent survey from the sub-continent (India) had showed close to 80% of the rehabilitation facilities with basic tele-rehabilitation infrastructure ( 16 ). However, tele-health and rehabilitation services are not available and are poorly utilized by the government primary care systems in many countries in the region of Sub-Saharan Africa ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, close to 1/3 of the Brazilian population lack access to internet ( 27 ). Although the providers have access to basic tele-rehabilitation infrastructure like in India, the consumers need to have internet access to avail such services ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature exploring the impact of COVID-19 on people living with disabilities and older persons, those likely to require regular access to AT, is steadily increasing [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The impact of COVID-19 on AT providers, however, has been less commonly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Critical discussions are occurring in the literature regarding how health services might be transformed given pandemic restrictions [ 50 , 51 ], and how health professions may respond [ 50 , 51 , 52 ]. Data from this study provided some perspectives from AT users and families as to the capability and responsiveness of AT personnel (see other studies in this series) as well as the impacts of the loss of other personnel (community-based rehabilitation workers, volunteers, school staff, community members) upon their health, development, and wellbeing.…”
Section: Discussionmentioning
confidence: 99%